2014
DOI: 10.1007/s10533-014-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium silicate treatment on the composition of forest floor organic matter in a northern hardwood forest stand

Abstract: Overall, our results suggest that added Ca and/or Si may react with SOM to reduce the accessibility of labile C forms to soil microbes.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…At Woods Lake, approximately four times more Ca was applied in the liming treatment than at Hubbard Brook, but increases in soil pH were roughly comparable. Also, in plotscale CaSiO 3 -enrichment studies at HBEF, where the levels of enrichment were five times higher than in the watershed experiment, researchers found decreased SOC solubility (Balaria et al 2015) and decreased decomposition of older SOC, despite higher leaf litter turnover (Minick et al 2017).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…At Woods Lake, approximately four times more Ca was applied in the liming treatment than at Hubbard Brook, but increases in soil pH were roughly comparable. Also, in plotscale CaSiO 3 -enrichment studies at HBEF, where the levels of enrichment were five times higher than in the watershed experiment, researchers found decreased SOC solubility (Balaria et al 2015) and decreased decomposition of older SOC, despite higher leaf litter turnover (Minick et al 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Also, in plot‐scale CaSiO 3 ‐enrichment studies at HBEF, where the levels of enrichment were five times higher than in the watershed experiment, researchers found decreased SOC solubility (Balaria et al. ) and decreased decomposition of older SOC, despite higher leaf litter turnover (Minick et al. ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A series of studies from Syracuse University over the last decade has shown that the application of calcium silicate (wollastonite) can also help in increasing soil organic matter (SOM) in forested soil, as well as contributing to nutrient management by increasing exchangeable calcium, thereby improving the pH of the nutrient-depleted, acidic forest soil [37][38][39]. Wollastonite is used as a liming agent for the forest soil to improve the soil fertility, but these studies have not looked at inorganic carbon sequestration potential of this silicate mineral.…”
Section: Soil Carbon Sequestration As Socmentioning
confidence: 99%